2018
DOI: 10.1002/14651858.cd010893.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Interventions for reducing inflammation in familial Mediterranean fever

Abstract: Analysis 1.1. Comparison 1 Colchicine versus placebo, Outcome 1 Number of participants experiencing an attack.. Analysis 2.1. Comparison 2 Rilonacept versus placebo, Outcome 1 Number of participants experiencing an attack.. Analysis 3.1. Comparison 3 ImmunoGuard™ versus placebo, Outcome 1 Acute phase response.. .. .. .. Analysis 4.1. Comparison 4 Anakinra versus placebo, Outcome 1 Number of participants experiencing an attack.. Analysis 4.2. Comparison 4 Anakinra versus placebo, Outcome 2 Drug-related adverse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 80 publications
0
8
0
2
Order By: Relevance
“…A Cochrane review evaluating drugs used for colchicineresistant FMF (anakinra, rilonacept, etanercept, infliximab, thalidomide, IFN-alpha, herbal dietary supplements, and non-steroidal anti-inflammatory drugs) concluded that there were still limited randomized controlled studies for the treatment of FMF. 9 Few studies consisting of limited cases showed benefits with IFN-alpha. IFN prevented most of the FMF attacks or attenuated the attack intensity.…”
Section: Discussionmentioning
confidence: 99%
“…A Cochrane review evaluating drugs used for colchicineresistant FMF (anakinra, rilonacept, etanercept, infliximab, thalidomide, IFN-alpha, herbal dietary supplements, and non-steroidal anti-inflammatory drugs) concluded that there were still limited randomized controlled studies for the treatment of FMF. 9 Few studies consisting of limited cases showed benefits with IFN-alpha. IFN prevented most of the FMF attacks or attenuated the attack intensity.…”
Section: Discussionmentioning
confidence: 99%
“…Захворювання має переваж не поширення у середземноморській популяції з характерними клінічними ознаками. Колхіцин розглядають як препарат пер шої лінії для стандартного лікування сімейної середземномор ської лихоманки [6][7][8]. У 87% випадків його застосування значно зменшує тяжкість перебігу, тривалість загострення та частоту нападів [30,31].…”
Section: сімейна середземноморська лихоманкаunclassified
“…
Редакція журналу «Український медичний часопис» Анотація. Колхіцин як потужний протизапальний препарат давно і активно застосовують у ревматології, переважно для лі кування пацієнтів із подагрою, а також при системних васкулітах, хворобі Бехчета та сімейній середземноморській лихо манці [1][2][3][4][5][6][7][8]. Однак потенціал протизапальних можливостей колхіцину далеко не вичерпаний.
…”
unclassified
“…2015, Wu et al . 2018), and could theoretically reduce the consequences of SPAID by blocking amyloid deposition and serum amyloid A synthesis, downregulation of inflammatory pathways, and modulation of innate immunity (Livneh et al . 1994, Leung et al .…”
Section: Introductionmentioning
confidence: 99%